THE EFFECT OF USING LOCAL WISDOM-BASED READING MATERIALS ON THE STUDENTS’ READING COMPREHENSION - Sastrawati, Ika (Study Program of English Literature, 2019)
Reading is one of the skills that should be improved by the students in learning English. The implementation of local wisdom based reading in this current research aimed to find out to what extent the effect of local wisdom based reading toward students’ reading comprehension at tenth grade students of SMA Muhammadiyah 1 Makassar. In this research, the researcher used experimental method with pre-experimental design. There were two kinds of test, namely pretest and posttest. Besides, the researcher administered the questionnaire to find out the students’ responds toward the effect of local wisdom based reading. The number of sample used in this research was 22 students. The result of this research shows that local wisdom based reading materials positively influenced the students’ reading comprehension. It is proved by the students’ mean score in pretest was 45.00 and posttest was 69.95. in addition, the result of the questionnaire shows that there were about 72.73% students give positive respond toward the material applied